2006
DOI: 10.1093/ajcn/84.3.616
|View full text |Cite
|
Sign up to set email alerts
|

Low serum concentrations of 25-hydroxyvitamin D in older persons and the risk of nursing home admission

Abstract: Lower serum 25(OH)D concentrations in older persons are associated with a greater risk of future nursing home admission and may be associated with mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
2
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(95 citation statements)
references
References 54 publications
5
84
2
4
Order By: Relevance
“…Higher levels than this do not appear to offer any additional beneficial effect regarding the risk of falling. 81 Thus, most of the current literature data concur that vitamin D deficiency leads to myopathy, reduced muscle mass and strength, low exercise performance and an increased risk of falling, 83 while higher vitamin D levels have been associated with improved balance, reduced frailty and disability, 84,85 maintenance of functional independence 86 and better mobility. 53,87,88 other major trials have also confirmed that vitamin D supplementation lowers the risk of falling and fractures in the elderly.…”
Section: Association Between Low Vitamin D Levels and The Risk Of Falmentioning
confidence: 98%
“…Higher levels than this do not appear to offer any additional beneficial effect regarding the risk of falling. 81 Thus, most of the current literature data concur that vitamin D deficiency leads to myopathy, reduced muscle mass and strength, low exercise performance and an increased risk of falling, 83 while higher vitamin D levels have been associated with improved balance, reduced frailty and disability, 84,85 maintenance of functional independence 86 and better mobility. 53,87,88 other major trials have also confirmed that vitamin D supplementation lowers the risk of falling and fractures in the elderly.…”
Section: Association Between Low Vitamin D Levels and The Risk Of Falmentioning
confidence: 98%
“…This analysis has stimulated other researchers of cohort studies to include allcause mortality as an outcome, along with CVD (Table 3). Surprisingly, the first cohort study to report on the association between baseline 25(OH)D levels and subsequent risk of death, which was from the Netherlands, was missed in the subsequent rush of papers on this topic, perhaps because its focus was on predicting admission to nursing homes rather than death (126) . However, since then, eleven other cohort studies have reported on this association (Table 3) (97,(99)(100)(101)(102)(103)105,106,(127)(128)(129) .…”
Section: All-cause Mortalitymentioning
confidence: 99%
“…Several population-based studies have reported vitamin D status in age groups from children to centenarians, as well as in isolated groups of individuals with discrete diseases (11)(12)(13)(14)(15). Individuals who would otherwise be considered healthy typically have serum 25(OH)D levels averaging in the range of 50 to 65 nmol/L, and from 65 to 100% of such populations have levels Ͻ80 nmol/L.…”
Section: Prevailing Vitamin D Statusmentioning
confidence: 99%